2017
DOI: 10.1016/j.dnarep.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of RAD51AP1 in homologous recombination DNA repair and carcinogenesis

Abstract: Homologous recombination (HR) serves to repair DNA double-strand breaks and damaged replication forks and is essential for maintaining genome stability and tumor suppression. HR capacity also determines the efficacy of anticancer therapy. Hence, there is an urgent need to better understand all HR proteins and sub-pathways. An emerging protein that is critical for RAD51-mediated HR is RAD51-associated protein 1 (RAD51AP1). Although much has been learned about its biochemical attributes, the precise molecular ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 63 publications
1
35
1
Order By: Relevance
“…A former study highlighted the potential of targeting RAD51 as a new and effective therapeutic strategy for NSCLC . RAD51AP1 is a DNA‐binding protein that could stimulate the activity of RAD51 , which plays an important role in RAD51 ‐mediated homologous recombination . Existing literature has revealed that RAD51AP1 is highly expressed in ovarian and lung cancers, and silencing RAD51AP1 has an inhibitory effect on ovarian and lung cancer cell proliferation in vitro through RNA interference .…”
Section: Introductionmentioning
confidence: 99%
“…A former study highlighted the potential of targeting RAD51 as a new and effective therapeutic strategy for NSCLC . RAD51AP1 is a DNA‐binding protein that could stimulate the activity of RAD51 , which plays an important role in RAD51 ‐mediated homologous recombination . Existing literature has revealed that RAD51AP1 is highly expressed in ovarian and lung cancers, and silencing RAD51AP1 has an inhibitory effect on ovarian and lung cancer cell proliferation in vitro through RNA interference .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the high expression of RAD51AP1 is associated with poor prognosis in patients with breast and ovarian cancer [34]. In some tumor cells and tissues, the increased RAD51AP1 may be related to the advantages of selective growth, enabling the replication of early tumor cells and metastatic cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…When the doublestranded structure of DNA is injured, RAD51 exploits a sister DNA molecule as a template that allows for homologous recombination (HR) in the damaged region, which maintains the stability of the genes [4]. While RAD51 displays a protective role, scholars have found that RAD51 is overexpressed in several tumor types, including breast, pancreatic, head and neck, prostate, non-small cell lung, and esophageal cancers [5,6]. Recently, Yuan et al [7] discovered that high RAD51 expression was directly associated with increased chemoand radio-resistance, along with dismal outcomes and prognoses in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%